Raj and the best day ever! - Braun, Sébastien (Templar Books, 2019)
"Raj and Dad are going on an adventure. They plan a list of all the things they will do. But then disaster strikes! Dad has left his wallet at home, and Raj thinks their day will be ruined. But maybe Raj and Dad can still have a great day--all they need is their imaginations and each other's company!" --
Keywords: Tiger / Juvenile fiction; Fathers and sons / Juvenile fiction; Children's stories; Picture books for children; Tiger / Fiction; Fathers and sons / Fiction; Children's Books/Ages 4-8 Fiction; Family - Parents; Social Themes - Emotions & Feelings; Concepts - Money; Tigre / Romans, nouvelles, etc. pour la jeunesse; Pères et fils / Romans, nouvelles, etc. pour la jeunesse; Histoires pour enfants; Livres d'images pour enfants; JUVENILE FICTION / Family / Parents; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Animals / General; Fathers and sons; Tiger; Paper case bindings; Illustrated case bindings; book jackets; Illustrated endpapers; picture books; Fiction; Juvenile works; Picture books; Livres d'images; Bilderbuch